Hubungan Batas Cair dan Plastisitas Indeks Tanah Lempung yang Disubstitusi Pasir Terhadap Nilai Kohesi Tanah pada Uji Direct Shear - Ramadhani, Taufik; Iswan, Iswan; Jafri, Muhammad (Universitas Lampung, 2015)
The Clay has a low shear force properties, large density, small permeability coefficient and has alow bearing capacity. To increase the bearing capacity of the clay can be used a mixture of sand.In this study, the test is done by using the Direct Shear test, which will be a reference in relation ofliquid limit and plasticity index to the value of cohesion (c) of each soil sample that has beensubstituted with sand.Soil samples used an original soil samples and disturbed soil of clay that comes from threelocations: the area Margakaya Jati Agung South Lampung, Palputih Karang Anyar SouthLampung , and Belimbing Sari Jabung East Lampung. Clay will be mixed with sand No.40 sieve(0.43 mm) in accordance with the required percentage of the variation in sand content of 0%, 5%,10%, and 15%.Based on AASHTO classification system, the three of soil include to the class of ordinary clay soilup to bad as subgrade material. The addition of sand mixture into three types of clay causingdecreased shear strength. The greater the addition of sand content, then the value of cohesion (c),liquid limit and plasticity index of the soil will decrease and shear angle will increase.Keywords : shear strength, Atterberg limits, Clay, Sand .